2019
DOI: 10.1002/eat.23047
|View full text |Cite
|
Sign up to set email alerts
|

The central role of disgust in disorders of food avoidance

Abstract: Background Individuals with extreme food avoidance such as Avoidant Restrictive Food Intake Disorder (ARFID) experience impairing physical and mental health consequences from nutrition of insufficient variety or/and quantity. Identifying mechanisms contributing to food avoidance is essential to develop effective interventions. Anxiety figures prominently in theoretical models of food avoidance; however, there is limited evidence that repeated exposures to foods increases approach behavior in ARFID. Studying di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 61 publications
3
27
1
1
Order By: Relevance
“…In contrast to AN, patients with ARFID lack shape concerns, body image preoccupation, and drive for thinness (Norris, Spettigue, & Katzman, 2016; Schmidt, Vogel, Hiemisch, Kiess, & Hilbert, 2018). Instead, they often have a narrow range of accepted foods based on taste, texture, colour, appearance, or odour, a fear of swallowing, choking or vomiting, and/or a lack of interest in food or disgust (Harris et al, 2019; Mammel & Ornstein, 2017; Norris et al, 2018; Reilly, Brown, Gray, Kaye, & Menzel, 2019; Zickgraf, Lane‐Loney, Essayli, & Ornstein, 2019). Generally, ARFID has a higher prevalence in younger children and boys than other eating disorders and is frequently associated with concurrent physical and psychological symptoms and lower quality of life (Fisher et al, 2014; Krom et al, 2019; Nicely, Lane‐Loney, Masciulli, Hollenbeak, & Ornstein, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to AN, patients with ARFID lack shape concerns, body image preoccupation, and drive for thinness (Norris, Spettigue, & Katzman, 2016; Schmidt, Vogel, Hiemisch, Kiess, & Hilbert, 2018). Instead, they often have a narrow range of accepted foods based on taste, texture, colour, appearance, or odour, a fear of swallowing, choking or vomiting, and/or a lack of interest in food or disgust (Harris et al, 2019; Mammel & Ornstein, 2017; Norris et al, 2018; Reilly, Brown, Gray, Kaye, & Menzel, 2019; Zickgraf, Lane‐Loney, Essayli, & Ornstein, 2019). Generally, ARFID has a higher prevalence in younger children and boys than other eating disorders and is frequently associated with concurrent physical and psychological symptoms and lower quality of life (Fisher et al, 2014; Krom et al, 2019; Nicely, Lane‐Loney, Masciulli, Hollenbeak, & Ornstein, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Future work would be expected to provide more clarity to this debate. Notwithstanding, if future research further supports this conceptualization, it would have important clinical implications in that disorders for which disgust is a core component had been missed because of low scores on measures developed in accordance with the cultural evolution or adaptationist models (e.g., food disgust in avoidant restrictive food intake disorder; Harris et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Recently there has been renewed focus on taste perception, specifically disgust in the context of food avoidance. Harris et al () found in a survey across a large cohort of adult individuals that measures for disgust were closely related to anxiety in avoidant restrictive food intake disorder. This led to the hypothesis that sensory sensitivity could be a risk factor for food avoidance behaviors and if we can identify the underlying mechanism or neurobiology we could develop a novel target for treatment (Menzel, Reilly, Luo, & Kaye, ).…”
Section: The Role Of Taste Perceptionmentioning
confidence: 99%